Arctic stratospheric dehydration – Part 2: Microphysical modeling - Engel, I.; Luo, B. P.; Khaykin, S. M.; Wienhold, F. G.; Vömel, H.; Kivi, R.; Hoyle, C. R.; Grooß, J.-U.; Pitts, M. C.; Peter, T. (Atmospheric Chemistry and Physics, 2014)
Large areas of synoptic-scale ice PSCs (polar stratospheric clouds) distinguished the Arctic winter 2009/2010 from other years and revealed unprecedented evidence of water redistribution in the stratosphere. A unique snapshot of water vapor repartitioning into ice particles was obtained under extremely cold Arctic conditions with temperatures around 183 K. Balloon-borne, aircraft and satellite-based measurements suggest that synoptic-scale ice PSCs and concurrent reductions and enhancements in water vapor are tightly linked with the observed de- and rehydration signatures, respectively. In a companion paper (Part 1), water vapor and aerosol backscatter measurements from the RECONCILE (Reconciliation of essential process parameters for an enhanced predictability of Arctic stratospheric ozone loss and its climate interactions) and LAPBIAT-II (Lapland Atmosphere–Biosphere Facility) field campaigns have been analyzed in detail. This paper uses a column version of the Zurich Optical and Microphysical box Model (ZOMM) including newly developed NAT (nitric acid trihydrate) and ice nucleation parameterizations. Particle sedimentation is calculated in order to simulate the vertical redistribution of chemical species such as water and nitric acid. Despite limitations given by wind shear and uncertainties in the initial water vapor profile, the column modeling unequivocally shows that (1) accounting for small-scale temperature fluctuations along the trajectories is essential in order to reach agreement between simulated optical cloud properties and observations, and (2) the use of recently developed heterogeneous ice nucleation parameterizations allows the reproduction of the observed signatures of de- and rehydration. Conversely, the vertical redistribution of water measured cannot be explained in terms of homogeneous nucleation of ice clouds, whose particle radii remain too small to cause significant dehydration.